Ways of shaping love for God and people and historical memory during the Year of St. Stanislaus Kostka - Kućko, Wojciech (Kwartalnik Naukowy Fides et Ratio, 2022)
The aim of the article is to show the many various ways in which the Year of St. Stanislaus Kostka, announced in 2018 on the occasion of the 450th anniversary of his death, was celebrated, and how were the ways of shaping love for God and people during that time. The article presents a review of the most important facts about the main jubilee celebrations in Poland and abroad which were also possibilities to build the historical memory. The year of St. Stanislaus Kostka was part of a long tradition of celebrations marking the anniversaries of this patron saint of Poland, held since the year of his beatification (1602/1605), and more solemnly since his canonization in 1726. The text discusses the worldwide and nationwide events commemorating the Saint of Rostkowo, and presents the main publications and conferences devoted to this saint. It also mentions the exhibitions and various pastoral initiatives taken during the year. Particular attention has been paid to celebrations in the Diocese of Płock, where Rostkowo, the birthplace of St. Stanislaus Kostka, is located. On this basis, the pertinence of the saint’s message has been discussed as well.